Reduced Interhemispheric Functional Connectivity in the Motor Cortex during Rest in Limb-Onset Amyotrophic Lateral Sclerosis - Jelsone-Swain, Laura M.; Fling, Brett W.; Seidler, Rachael D.; Hovatter, Rebecca; Gruis, Kirsten; Welsh, Robert C. (Frontiers in Systems Neuroscience, 2010)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder of motor neurons that leads to paralysis and eventually death. There is evidence that atrophy occurs in the primary motor cortex (M1), but it is unclear how the disease affects the intrinsic connectivity of this structure. Thus, the goal of this study was to examine interhemispheric coupling of low frequency blood-oxygen-level dependent (BOLD) signal fluctuations in M1 using functional connectivity magnetic resonance imaging (fcMRI) during rest. Because disease progression is rapid, high-functioning patients were recruited to assess neural changes in the relatively early stages of ALS. Twenty patients with limb-onset ALS participated in this study. A parceling technique was employed to segment both precentral gyri into multiple regions of interest (ROI), thus increasing sensitivity to detect changes that exist along discretely localized regions of the motor cortex. We report an overall systemic decrease in functional connectivity between right and left motor cortices in patients with limb-onset ALS. Additionally, we observed a pronounced disconnection between dorsal ROI pairs in the ALS group compared to the healthy control group. Furthermore, measures of limb functioning correlated with the connectivity data from dorsal ROI pairs, suggesting a symptomatic relationship with interhemispheric M1 connectivity.